A Juridical Examination of the Criminal Liability of Persons with Physical Disabilities in Sexual Violence Cases in Indonesia - I Gede K Ananta Yoga; I Made Wirya Darma (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Sexual violence is a serious crime that produces multidimensional impacts, including physical, psychological, and social harm. The complexity increases when offenders are persons with physical disabilities. This article aims to analyze the criminal liability of such offenders through a normative review of court decisions and to propose normative solutions for achieving substantive justice. The research employs a normative legal method using statutory, conceptual, and case approaches, specifically examining Indonesian criminal law, applying the theories of John Rawls, Philipus M. Hadjon, and Roscoe Pound, and analyzing the Ambon District Court Decision No. 236/Pid.Sus/2024 and the Mataram District Court Decision No. 23/Pid.Sus/2025. The findings confirm that physical disability does not negate criminal liability since actus reus and mens rea remain fulfilled. However, disability has not been proportionally considered in sentencing, resulting in merely formal justice. The study recommends normative reform, technical guidelines for law enforcement, and disability-friendly correctional facilities to ensure proportionality, prevent discrimination, and uphold human rights. The research implications suggest that these recommendations can serve as a foundation for policymakers to strengthen legal frameworks, provide practical guidance for law enforcement officers in handling cases involving persons with disabilities, and encourage the development of more inclusive correctional institutions. Moreover, the findings highlight the importance of aligning national practices with international human rights standards, which may inspire further comparative studies and reforms in other jurisdictions.